PSYCHOLOGICAL IMPACT OF CHEMOTHERAPY AND SUPPORTIVE-EDUCATIVE DISCUSSION GROUP WITH SPIRITUAL CARE APPROACH TO CANCER PATIENT - Nurul Rezki Anisa; Liza Fauzia; Anwar Ganing (JIK-JURNAL ILMU KESEHATAN, 2022)
Breast cancer has complications and a poor prognosis. Although chemotherapy treatment for breast cancer shows an increase in survival, this also contributes to a prolonged period of medical intervention which also results in physical and especially psychological complaints of the patient. Hope is one of the important elements for patients to survive with a breast cancer diagnosis. Having friends, mentors, communities, or social groups in the Supportive-Educative Discussion Group (SEDG) can be effective increasing hope for healing, reducing loneliness, and improving the quality of life of patients. This study aims to determine the level of stress on chemotherapy treatment and the effectiveness of SEDG with a spiritual care approach in reducing stress. This research method used a quasi-experimental pre-post test design with DASS 42 questionnaire. Data was collected through a focused group discussion on 30 breast cancer patients, bivariate analysis using Kendal's Tau C test. The results of this study showed a decrease in the stress level of cancer patients after following the SEDG. This study also indicated that a spiritual approach had a positive effect on patient stress. However, it is necessary to further identify the factors that cause stress in breast cancer patients in addition facing chemotherapy